The Effects of Lycopene on the Methylation of the GSTP1 Promoter and Global Methylation in Prostatic Cancer Cell Lines PC3 and LNCaP. (20th October 2014) - Fu, Li-Juan; Ding, Yu-Bin; Wu, Lan-Xiang; Wen, Chun-Jie; Qu, Qiang; Zhang, Xue; Zhou, Hong-Hao
Abstract : DNA (cytosine-5-) methylation silencing of GSTP1 function occurs in prostate adenocarcinoma (PCa). Previous studies have shown that there is an inverse relationship between dietary lycopene intake and the risk of PCa. However, it is unknown whether lycopene reactivates the tumor suppressor gene glutathioneS-transferase- π (GSTP1) by demethylation of the hypermethylated CpGs that act to silence the GSTP1 promoter. Here, we demonstrated that lycopene treatment significantly decreased the methylation levels of the GSTP1 promoter and increased the mRNA and protein levels of GSTP1 in an androgen-independent PC-3 cell line. In contrast, lycopene treatment did not demethylate the GSTP1 promoter or increase GSTP1 expression in the androgen-dependent LNCaP cell line. DNA methyltransferase (DNMT) 3A protein levels were downregulated in PC-3 cells following lycopene treatment; however, DNMT1 and DNMT3B levels were unchanged. Furthermore, the long interspersed element (LINE-1) and short interspersed element ALU were not demethylated when treated by lycopene. In LNCaP cells, lycopene treatment did not affect any detected DNMT protein expression, and the methylation levels of LINE-1 and ALU were decreased. These results indicated that the protective effect of lycopene on the prostate is different between androgen-dependent and androgen-independent derived PCa cells. Further, in vivo studies should be conducted to confirm these promising results and to evaluate the potential role of lycopene in the protection of the prostate.